2015
DOI: 10.1080/2162402x.2015.1100789
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoints programmed death 1 ligand 1 and cytotoxic T lymphocyte associated molecule 4 in gastric adenocarcinoma

Abstract: Remarkable efficacy of immune checkpoint inhibition has been reported for several types of solid tumors and early studies in gastric adenocarcinoma are promising. A detailed knowledge about the natural biology of immune checkpoints in gastric adenocarcinoma is essential for clinical and translational evaluation of these drugs. This study is a comprehensive analysis of cytotoxic T lymphocyte associated molecule 4 (CTLA-4) and programmed death 1 ligand 1 (PD-L1) expression in gastric adenocarcinoma. PD-L1 and CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 55 publications
(66 reference statements)
2
45
0
1
Order By: Relevance
“…ATF7IP/MCAF1 functions for either DNA methylation‐based gene repression or the transcription factor Sp1‐mediated gene activation . On the other hand, PD‐L1 is generally produced by cancer cells to escape immune surveillance, and is a molecular target for cancer immune therapy . Previous report showed that the PD‐L1 gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATF7IP/MCAF1 functions for either DNA methylation‐based gene repression or the transcription factor Sp1‐mediated gene activation . On the other hand, PD‐L1 is generally produced by cancer cells to escape immune surveillance, and is a molecular target for cancer immune therapy . Previous report showed that the PD‐L1 gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells .…”
Section: Resultsmentioning
confidence: 99%
“…36 On the other hand, PD-L1 is generally produced by cancer cells to escape immune surveillance, and is a molecular target for cancer immune therapy. [41][42][43] Previous report showed that the PD-L1gene promoter is regulated by DNA methylation or Sp1 binding in cancer cells. 44,45 There is the possibility that ATF7IP/MCAF1 may control PD-L1 expression via Sp1,as indicated by published ChIP-seq data of colon cancer ( Figure S3A).…”
Section: Expression Levels Of Nuclear Atf7ip/ Mcaf1 Are Correlated mentioning
confidence: 99%
“…The CD8 þ TILs are the main aggressors involved in killing tumor cells, but PD-1/PD-L1 is one of the immune checkpoints underlying immunologic evasion of tumors (1). In regard to functional relationships among the immune checkpoints (35,36), we suggest that more comprehensive analysis with other kinds of immune checkpoints would provide more information. Although PD-L1 expression in tumor-infiltrating immune cells, such as macrophages and lymphocytes, has been evaluated recently, the expression on lymphocytes was not sufficiently observed in our paraffin-embedded tissues.…”
Section: Cd8 D8mentioning
confidence: 99%
“…17 To assess the impact of immune escape on tumor associated B cell subsets, we analyzed loss of HLA-I (HLA-ABC) and expression of PD-L1 as two mechanisms of immune evasion described in gastroesophageal adenocarcinoma. 18,19 Altered HLA-expression with either partial or complete loss was detected in 6/27 (22.2%) of primary tumor samples ( Figure 5A, C). Immunohistochemistry showed positive staining for PD-L1 on tumor cells or tumor infiltrating lymphocytes in 16/27 (59.3%) of analyzed samples (Figure 5B, C).…”
Section: B Cell Infiltrates Are Decreased In Tumors Containing Factormentioning
confidence: 99%